MiR‐22‐3p in exosomes increases the risk of heart failure after down‐regulation of FURIN. (28th November 2022) - Lu, Wenlin; Liu, Xuhui; Zhao, Linghui; Yan, Shirong; Song, Qingyun; Zou, Cao; Li, Xun
Abstract: Heart failure (HF) is often the inevitable manifestation of myocardial ischemia. Hypoxia can induce cardiomyocytes to express many microRNAs (miRNAs), which are highly expressed in exosomes. In addition, miR‐22‐3p is a marker in heart failure. Therefore, miR‐22‐3p was taken as the research object to explore its role and mechanism in HF. HF differentially expressed miRNAs were screened by bioinformatic analysis. The HF rats model was constructed and identified by detecting serum brain natriuretic peptide (BNP) and ultrasound analysis [left ventricular ejection fraction (LVEF) and left ventricular fractional shortening (LVFS)]. The extracted exosomes were identified by transmission electron microscopy, and Western blot was used to detect the expressions of Tsg101 and CD63. Quantitative real‐time polymerase chain reaction detected miR‐22‐3p expression in serum, exosomes, and serum without exosomes, while the cardiomyocytes cytotoxicity was detected by 3‐(4, 5‐dimethyl‐2‐thiazolyl)‐2, 5‐diphenyl‐2‐H‐tetrazolium bromide (MTT) and PKH26 staining. After overexpressing/silencing miR‐22‐3p in cells, cell viability, apoptosis, and apoptosis‐associated markers were detected. Bioinformatic analysis screened the target gene of miR‐22‐3p, which was verified by dual‐luciferase assay. Regulation of miR‐22‐3p on FURIN was measured by rescue tests. In vivo experiments were verified the above results. MiR‐22‐3p was identified as the research object. BNP was increased in the model group, while LVEF and LVFS were decreased. MiR‐22‐3p was overexpressed in HF‐treated serum and exosomes. Normal exosomes did not affect cardiomyocyte function, while high concentrations of HF‐treated exosomes were cytotoxic. By regulating apoptosis‐related genes, overexpressed miR‐22‐3p inhibited cell activity and promoted cell apoptosis. Silenced miR‐22‐3p with opposite effects counteracted effects of HF‐treated exosomes. FURIN, target gene of miR‐22‐3p, was negatively regulated by miR‐22‐3p, while overexpressed FURIN promoted cell activity and inhibited apoptosis. In vivo research was consistent with the results of cell experiments. By regulating FURIN, miR‐22‐3p in exosomes increases the risk of HF damage. Abstract : The miR‐22‐3p derived from exosomes increased cardiomyocyte apoptosis by inhibiting the expression of FURIN.